France : Financial and Real Sector Issues. (International Monetary Fund, 1995)
This book, edited by Paul R. Mason, analyses the policy challenges that face the French economy in the second half of this decade, highlighting the need for structural changes to enhance the economy's flexibility. The authors argue that budgetary constraints will oblige France to address structural economic problems by reducing social benefits and cutting government expediture.